High-temperature thermostatistical properties of deformed quantum gas in two dimensions - Mustafa Şenay (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In thisstudy, we focus on the high-temperature thermostatistical properties of the q-deformed gas model in two spatialdimensions. Some important thermodynamical functions such as internal energy,entropy, specific heat are calculated depending on deformation parameter q. Moreover, the first five deformedvirial coefficients in the equation of state of the model for two dimensionsare derived. Also, the results obtained in this work are compared with theresults of the undeformed gas model.